POLITICAL BRANDING PASANGAN CALON PRESIDEN MELALUI TIKTOK PADA KAMPANYE PEMILU 2024 - Aleda Maharany; Mia Dwianna Widyaningtyas (Universitas Sultan Ageng Tirtayasa, 2025)
In a political contestation, the candidates take part in branding to build an image in the eyes of the public, which is called political branding. Tiktok social media is used by presidential and vice presidential candidates in the 2024 elections to build political branding. This study aims to determine aspects of personality, appearance, and political messages on the accounts of the 2024 Election candidates represented in icons, indexes, and symbols. This research uses a qualitative approach, with Charles Sanders Peirce's semiotic analysis technique that examines icons, indices, and symbols. Political Branding is examined by looking at indicators from Mitsikopolou's (2008) theory which includes personality, appearance, and political messages. The research uses symbolic interaction theory to discuss findings related to communication symbols in campaigns on Tiktok Social Media. The object of this research is the Tiktok accounts @aniesbaswedan, @amuhaiminiskandar, @partaigerindra, @gibran_rakabuming, @ganjarpranowo, and @mohmahfudmdofficial. The unit of analysis is the upload of the candidates' campaign content on Tiktok from January 10 to February 10, 2024. Each candidate account selected 5 contents that have political branding elements. The results of this study show that each candidate displays various aspects of personality to be memorable in the minds and minds of the public, but almost all candidates emphasize the element of connection with the community. In the appearance aspect, the candidates show political branding symbols from the clothes they wear. From the aspect of political messages, the candidates' personal branding is shown in the form of communication and interaction with the community during the campaign.